Governança corporativa nas estatais: cerimônia ou algo mais? - Secco, Dany Andrey (2023)
This research addresses the internalization of corporate governance in four state owned companies and in two private companies, all members of the "Public Utility/Water and Sanitation" Sector of the Brazilian Stock Exchange (B3), from the perspectives of sociological new institutionalism and organizational anthropophagy. It was sought to evaluate how the structures and rules of corporate governance are reflected in the discourse contained in the minutes of the respective Boards of Directors, considering the period from 2015 to 2022. The methodology aimed, by counting the occurrences of themes that portrayed corporate governance, associated with the perspective of content analysis of Bardin (1977), to verify the ceremony that involved the adoption of the myth of corporate governance and whether there was a manifest presence of substantive needs for the adoption of the exogenous model in the discourse of the Boards of Directors. In general, Copasa, Sanepar and Casan demonstrated that there is a new behavior, a new agenda, another circulation of information within these state-owned companies, all this provoked by the adoption of corporate governance. In other words, the minutes show that a whole new ceremony was adopted for the communication of the Boards of Directors’ activities. On the other hand, Sabesp, Ambipar and Orizon were not concerned in communicating, ceremonially, the adoption of the myth, and limited themselves to comply, formally, with the rules to which they are submitted. In view of the results found, new studies are suggested to evaluate if there are different consequences of legitimacy gain between an organization that formally assumes a myth and one that ceremonially proclaims that it has adopted it.